Analisis Pengaruh Intensitas Cahaya Matahari dan Jenis Generator terhadap Kinerja Sistem Panel Surya-Generator Hidrogen 50 Wp - Saddam Firly Mustarisiam; Rifky; Tasyrik Al Qaida; Dicky Wyldan Putra Permana; Rezha Apriansyah (Prosiding Seminar Nasional Teknoka, 2025)
Hydrogen gas can be produced from wet hydrogen generators (GHB) and dry hydrogen generators (GHK). Both hydrogen generators are powered by a 50 Wp solar panel (PV). The aim of this research is to study the performance comparison of GHB and GHK in producing hydrogen gas flow rate and system efficiency to determine the more optimal system. The research began with a literature study and designing both generators, which underwent trials to obtain a research equipment system that adheres to the theory and concepts of GHB and GHK. Experimental methods were carried out by direct measurements of input and output variables from the solar panel as well as output variables from the GHB and GHK electrolysis systems. The research results show that the integrated PV-GHB system produces a larger hydrogen gas flow rate and higher system performance efficiency compared to PV-GHK.